Mainali’s “A Blaze in the Straw” as a Fine Work of Art - Paudel, Rudra Prasad (Tribhuvan University Journal, 2010)
Art refers to the product of creative human activity in which concepts are shaped and selected to convey an idea or emotion. A short story is an art form, a particular type of artistic activity and a product of the author’s imagination. Unlike novels that usually depict conflicts among many characters, developed through a variety of episodes, stimulating a complexity of responses inreaders, a short story is a brief fictional narrative prose disclosing one character’s inner conflict with others having one thematic focus. It concisely presents events and stirs our imagination. Guru Prasad Mainali (1900-1971), one of the prominent writers and a leading personality in Nepali literature, develops the modern short story in Nepali language and becomes popular with a few stories. His most famous stories have been collected in The Ward (Naso) (1969) in which an elderly Brahman who has no children is obliged to marry a second wife in order to clear his way to paradise. He writes stories in a new model and each is considered a classic. He isa modern artist in Nepali short story writing. In “A Blaze in the Straw,” Mainali focuses on a way of living of husband and wife in Nepali context and proves that the quarrel between husband and wife is not more than a blaze in the straw as shown in the life of Chame and Gaunthali. He, very skillfully, expresses the experience of the characters as it is, which is the greatness of the artist suggested in the art. Based on this fact, this article discusses Guru Prasad Mainali as a modern artist and his “A Blaze in the Straw” as Nepali proverb implied in the title.